Active Work Zone Safety: Preventing Accidents Using Intrusion Sensing Technologies - Awolusi, Ibukun; Marks, Eric D. (Frontiers in Built Environment, 2019)
Highway construction work zones are hazardous environments characterized by a dynamic and limited workspace. A host of interactions between workers, passing commuter vehicles, and moving construction equipment occurs in highway work zones, fostering dangerous situations that can result in injury or death. Active strategies, such as the deployment of intrusion sensing and alert technologies in highway work zones and in transportation infrastructure construction and maintenance, can be effective at mitigating these unforeseen conditions. The main objective of this study was to conduct both conceptual analysis and experimental evaluation of intrusion sensing technologies for work zone safety. To achieve the objectives of this research, an exploratory review of the applicable technologies was conducted to identify the intrusion technologies that can be implemented for work zone safety. An objective assessment of each technology was provided based on selected evaluation metrics to elicit their capabilities. Candidate commercially available technologies were selected and evaluated using field experiments in simulated work zones. The findings of the study indicate that the commercially available technologies have the potential to enhance safety of work zone workers by providing warning alerts when hazardous situations exist. This research contributes to the body of knowledge by providing strategies for selecting and implementing intrusion sensing technologies for active work zone safety.